TRANSFORMASI BATIK DAN GLOBALISASI - Suyin Pramono; Setiawan Sabana; Achmad Haldani (Universitas Trisakti, 2018)
Abstract Lately, we have noticed there are many changes in all fields. Therefore, it is suitable for “globalization” to be the main topic in this study, which is interpreted as a process where humans are vastly interconnected through various ways. From a cultural point of view,